A Perancangan Prototipe Monitoring Ketinggian Air Berbasis IoT Menggunakan Panel Surya Sebagai Sumber Energi Listrik - Sari, Tyas Kartika; Novita, Dianing; Abduh, Syamsir; Widjaja, Maulasukma (Website, 2023)
The high pollution and flooding in the rainy season is one of the problems faced by big cities in Indonesia, especially the capital city DKI Jakarta. To be able to reduce pollution and the effect of greenhouse gases, one way is to use environmentally friendly energy sources. The use of solar panels as an alternative source of electrical energy is an alternative to reduce the use of fossil energy. Based on these problems, the purpose of this research is to design a photovoltaic system for monitoring water levels based on IoT. The benefit that can be obtained from this research is that the river water level can be monitored in real time using an IoT-based water level monitoring prototype. Furthermore, designing prototypes and IoT systems can be carried out, in this study Arduino, web and also android applications are used. The alarm will turn on if the deep water level is above the predetermined limit. In the prototype there are three color LED lights as an indicator to mark the water level, the green color indicates that the water level is safe, the yellow color indicates that the water level is close to the safe limit and the red color indicates that the water level is above the limit. safe and dangerous. Key Word : Photovoltaic, flood, pollution, monitoring, IoT